Organizational Management and Personnel Islamic Education - Muhidin; Sopiansyah, Deni; Erihadiana, Mohammad (Journal of Islamicate Studies, 2020)
This research tries to discuss related to organizational management and personnel of Islamic education. The approach used in this study is a qualitative approach. The reason for using a qualitative approach is because this research was conducted to obtain an in-depth picture of the organization and personnel of Islamic education. This research is designed in the form of library research which uses various sources of literature as a source of research data. This research is a study related to the thought of a character in a certain period of time, so that the methodological approach used is the content approach. This study concludes that personnel management is manifested in clear job descriptions to create overlapping jobs. This personnel management starts from the stage of the employee procurement plan, placement, evaluation, repairs, compensation, employees to employee traffic jams. This is done to obtain profiles of employees who truly have qualifications in terms of maximum expertise, skills, motivation and creativity.